The Effects of Annealing Temperature Dependence on the Doping of Titanium Dioxide (TiO2) and Reduced Graphene Oxide (rGO) for Perovskite Solar Cell Application - Rafidah, Kemat; Siti Kudnie, Sahari; Afiqah, Baharin (UNIMAP, 2020)
In the present study, reduced Graphene Oxide (rGO) was introduced to Titanium Dioxide (TiO2) as Electron Transport Layer (ETL) in Perovskite Solar Cell (PSC). TiO2 doped rGO (TiO2/rGO) was prepared by doping Titanium (IV) Oxide nanopowder as a precursor for TiO2 and chemically reduced Graphene Oxide (rGO). The TiO2/rGO was varied with different annealing temperature and the effects of electrical, structural and optical on TiO2/rGO of PSC were studied. The surface morphologies of TiO2/rGO thin films were characterized via X-Ray Diffraction (XRD). Meanwhile, Ultraviolet-visible spectroscopy (UV-Vis) was used to characterize the optical properties of TiO2/rGO thin films while current-voltage (I-V) analysis was measured by using Keithley Sourcemeter. Structural and morphological evidence from XRD results confirmed that the TiO2/rGO samples changes from anatase phase to rutile phase as the annealing temperature increased and the average crystalline size of TiO2/rGO thin films change with the TiO2 crystalline phase accordingly. The annealing temperature of 550℃ exhibits the larger grain size that results in better conductivity, higher light absorption and lower bandgap energy.